Burden of vision loss associated with eye disease in China 1990–2020: findings from the Global Burden of Disease Study 2015. Issue 2 (12th June 2017) - Wang, Bingsong; Congdon, Nathan; Bourne, Rupert; Li, Yichong; Cao, Kai; Zhao, Aiping; Yusufu, Mayinuer; Dong, Wenlan; Zhou, Maigeng; Wang, Ningli
Abstract : Aims: To assess the burden of vision loss due to eye disease in China between 1990 and 2015, and to predict the burden in 2020. Methods: Data from the GBD 2015 (Global Burden of Diseases, Injuries, and Risk Factors Study 2015) were used. The main outcome measures were prevalence and years lived with disability (YLDs) for vision loss due to cataract, glaucoma, macular degeneration, other vision loss, refraction and accommodation disorders and trachoma. Results: Prevalence for eye diseases increased steadily from 1990 to 2015, and will increase until 2020. From 1990 to 2015, the most common eye disorder was refraction and accommodation disorders. From 1990 to 2015, the vision loss burden due to eye disease decreased for those aged 0–14 years, and increased for those aged 15 years and above, with the most notable increases occurring among those aged 50 years and above. China ranked 10th when comparing YLDs for vision loss due to eye disease with the other members of the G20 (Group of Twenty, an international forum for the governments from 20 major economies) . Age-standardised YLD rates for vision loss due to eye disease declined in all 19 countries, except for China. The burden from vision loss due to eye disease ranked 12th and 11th among all causes of health loss in China in 1990 and 2015, respectively. Conclusion: Alone among major economies, China has experienced an increase in the burden of age-standardised vision loss from eye disease over the last two decades. In the future, China may expect a growing burden of vision loss due to population growth and ageing.